Cinetique De Fermentation De Trois Methodes De Production De Ferments De Racines De Manioc - Kakou, Abodjo Celah; Boli, Zamblé Bi Irié Abel; Kambire, Ollo; Koussemon, Marina; Koffi, Nevry Rose (European Scientific Journal, ESJ, 2017)
Fermentation plays an important role in the production of several foods. In Côte.d'ivoire, the preparation of several traditional mets of the manioc requires the use of the traditional leavens. Thus, the objective of this study is to compare the evolution of some biochemical and microbiological parameters during the preparation of three types of experimental leavens starting from the roots of varieties bitter and soft of manioc. On the whole, 36 samples of roots of manioc whose 18 of the bitter variety (IAC) and 18 of the soft variety (Bonoua) were the subject of this study. The variety of manioc and the method of acquisition the leavens influence the evolution of the parameters such as the pH, sugars, the growth of the micro-organisms whatever the type of leaven. The leavens of boiled manioc are richer in total sugars while the leavens of believed manioc are it for reducing sugars.